Integrating Basic Listening with Cross-Cultural Understanding in Early Childhood Education Curriculum - Nur Istiqamah (DZURRIYAT : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education serves as the cornerstone for developing language skills and socio-cultural competencies in the global era. This study aims to examine the integration of basic listening skills with cross-cultural understanding in early childhood education curricula. A qualitative descriptive design was employed, utilizing classroom observations, semi-structured interviews with early childhood teachers, and curriculum document analysis, with thematic coding and triangulation applied for data validation. The findings reveal that listening activities through stories, songs, and play not only enhanced children’s phonological awareness and language comprehension but also fostered empathy, tolerance, and cultural sensitivity. These results affirm that merging listening skills with cross-cultural understanding offers an innovative framework for early childhood curricula, with implications for cultivating communicative, inclusive, and globally competent future generations.